2013
DOI: 10.1186/1751-0147-55-84
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-linked immunosorbent assay for detection of avian influenza virus subtypes H5 and H7 antibodies

Abstract: BackgroundAvian influenza virus (AIV) subtypes H5 and H7 attracts particular attention because of the risk of their potential pathogenicity in poultry. The haemagglutination inhibition (HI) test is widely used as subtype specific test for serological diagnostics despite the laborious nature of this method. However, enzyme-linked immunosorbent assays (ELISAs) are being explored as an alternative test method.H5 and H7 specific monoclonal antibodies were experimentally raised and used in the development of inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
(49 reference statements)
0
13
0
2
Order By: Relevance
“…The two serological tests are sensitive and specific (Jensen et al . ), indicating that birds in the study areas were actually exposed to AI H5 as vaccination of poultry against AI in Nigeria was prohibited since 2006 (NADIS ; Jensen et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The two serological tests are sensitive and specific (Jensen et al . ), indicating that birds in the study areas were actually exposed to AI H5 as vaccination of poultry against AI in Nigeria was prohibited since 2006 (NADIS ; Jensen et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rNP-ELISA has the potential to detect chicken antibodies against different AIV subtypes, because this technique uses a highly conserved antigen (NP) among the different subtypes of AIV, as demonstrated the epitope prediction analysis of this study and the results from previous studies reported by (Jin et al, 2004;Upadhyay et al, 2009;Wu et al, 2007). Despite the current rNP-ELISA was not tested for the detection of anti-AIV antibodies of other avian species, the rNP can be used also as coat-antigen in other ELISA methods such as blocking-ELISAs to react with anti-NP monoclonal antibodies (Jensen et al, 2013) to replace the purified AIV particles obtained from AIV-infected SPF embryonated chicken eggs that are submitted to purification by ultra-centrifugation in sucrose gradient.…”
Section: Discussionmentioning
confidence: 51%
“…Porém, é um teste limitado para vários subtipos de HA do VIA e pode haver resultados positivos inespecíficos para amostras de aves não galiformes. Já o teste de ELISA é sensível, específico, estável e de baixo custo, depende de menor quantidade de preparações de antígeno e anticorpos, além de possibilitar a avaliação de um maior número de amostras em um curto período de tempo (JENSEN et al, 2013;WU et al, 2007;OIE, 2014;TERREGINO, 2008;SPACKMAN, 2008).…”
Section: Diagnóstico Sorológico Da Influenza Aviáriaunclassified
“…No caso do sorodiagnóstico da IA, os laboratórios geralmente usam o teste de ELISA como uma ferramenta de triagem e o teste AGID para confirmação dos resultados positivos (JENSEN et al, 2013;TESSARI, 2015;WU et al, 2007).…”
Section: Diagnóstico Sorológico Da Influenza Aviáriaunclassified